(untitled) (Psychology Travelogs, 2025)
The article examines coping behavior as a key element in ensuring the psychological security of military personnel during their service. It is determined that military service is one of the most stress-inducing professional fields, requiring a high level of resilience, adaptability, and the ability to manage stressful situations effectively. The focus is on the role of coping strategies in maintaining emotional stability and preventing negative consequences of stress, such as burnout and post-traumatic stress disorder. The study highlights the theoretical aspects of coping behavior, its classification, and mechanisms of formation under military conditions. Individual psychological and socio-demographic factors influencing the choice of coping strategies-such as age, gender, professional experience, and education level-are discussed. The main approaches to analyzing coping behavior in the context of military psychology are considered, including cognitive-behavioral, socio-cognitive, and interactive frameworks. Particular attention is given to the functions of coping strategies, notably their role in reducing anxiety levels, enhancing effective communication, and facilitating adaptation to extreme service conditions. The article also substantiates the importance of developing psychological training programs aimed at fostering and enhancing adaptive coping strategies to preserve the mental health of military personnel. The findings of the study can be applied to improve practical measures for psychological support of military personnel, optimize their adaptation to service duties, and minimize the effects of stress associated with professional tasks in extreme conditions.